Short-Term Effect of Topical Cetylated Fatty Acid on Early and Advanced Knee Osteoarthritis: A Multi-Center Study - Alarico ARIANI; Simone PARISI; Giacomo M GUIDELLI; Marco BARDELLI; Augusto BERTINI; Enrico FUSARO (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate if short-term topical treatment with cetylated fatty acid (CFA) cream reduces the detrimental effects of early and advanced knee osteoarthritis (OA). Patients and methods: The study included 113 patients (32 males, 81 females; median age 70.0 years; 95% CI: 69.0 to 71.4 years) with knee OA diagnosed according to American College of Rheumatology classification criteria. Each patient underwent knee X-rays, followed by a CFA topical treatment (two applications per day for one week). Before and after the treatment, patients completed a Western Ontario and McMaster Universities Osteoarthritis Index questionnaire. All knee X-rays were classified according to Kellgren-Lawrence scale. Results: After one week of treatment, decreased Western Ontario and McMaster Universities Osteoarthritis Index overall scores and sub-scale scores were observed in the whole cohort (p<0.005) and Kellgren-Lawrence scale grade 3 group (p<0.05). In the Kellgren-Lawrence scale grade 2 group, overall Western Ontario and McMaster Universities Osteoarthritis Index scores and pain and functional ability sub-scale scores improved (p<0.05). Conclusion: Administration of topical CFA may mitigate most common symptoms in knee OA. Our findings suggest that topical CFA is effective in all knee OA patients with slightly higher evidence for those with advanced disease.